The impact of different types of teaching videos on learning satisfaction and cognitive load / Tan Shaojie and Arshad Abd Samad - Tan, Shaojie; Abd Samad, Arshad (UiTM Press, 2022)
The development of information technology provides a variety of ways for humans to acquire knowledge. Among the more common information technology used in teaching and learning is the video. This research explores the concept of teaching videos of declarative knowledge and the influence of different types of teaching videos on learners' learning satisfaction and cognitive load. It first sorts out the related research of instructional videos through literature research, and attempts to comprehensively consider the manpower, material resources, and technical difficulties invested in the production process of several common types of instructional videos summarized through literature research. They are classified into three categories, namely low cost, medium cost and high cost. Then, the impacts of three common but different types of teaching videos with different production processes on the learning effect of learners are studied. The study is in an experimental environment, with college students as the research object, strictly controlling the number and time of video viewing by learners, first pre-testing the subjects, and then letting the subjects learn the video followed by a post-test.